2016
DOI: 10.3390/met6090217
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Cyclic Deformation in Bulk Metallic Glasses

Abstract: Abstract:In this paper, a systematic numerical simulation was performed to elucidate the damage mechanisms in bulk metallic glasses (BMGs) subjected to the tension-compression cyclic loading, and then the relation between fatigue life, applied strain, and cycling frequency was therefore presented. The free volume was selected as an internal state variable to depict the shear-band nucleation, growth, and coalescence with the help of free volume theory, which was incorporated into the ABAQUS code via a user mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
(34 reference statements)
1
15
1
Order By: Relevance
“…On the other hand, it was shown that large strain cycles cause irreversible relaxations in the material and relocate the system to shallower energy minima, thus, leading to rejuvenation [40]. In the present study, the potential energy per particle in one representative sample is plotted where it was shown that after a certain number of cycles, the stress amplitude is reduced concomitantly with the initiation of a shear band across the sample [33,34]. We also comment that the transition from reversible dynamics at γ 0 = 0.07 to the plastic regime at γ 0 = 0.08 occurs at higher strain amplitudes than the critical value γ 0 = 0.06 reported in the previous MD study [10], where simulations were performed at the higher oscillation frequency ωτ = 0.02 and higher temperature T LJ = 0.1 ε/k B .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, it was shown that large strain cycles cause irreversible relaxations in the material and relocate the system to shallower energy minima, thus, leading to rejuvenation [40]. In the present study, the potential energy per particle in one representative sample is plotted where it was shown that after a certain number of cycles, the stress amplitude is reduced concomitantly with the initiation of a shear band across the sample [33,34]. We also comment that the transition from reversible dynamics at γ 0 = 0.07 to the plastic regime at γ 0 = 0.08 occurs at higher strain amplitudes than the critical value γ 0 = 0.06 reported in the previous MD study [10], where simulations were performed at the higher oscillation frequency ωτ = 0.02 and higher temperature T LJ = 0.1 ε/k B .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the amplitude of stress oscillations is reduced after the first several cycles, which is associated with the formation of a dominant shear band across the whole system [33,34]. In this process, the initiation of a shear band is preceded by an accumulation of shear transformation zones at the surface of the material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another work by MD simulation found that the localization of shear transformation zone obeys a power law with rate under tension-compression fatigue simulation [12]. By finite element method (FEM), Jiang [13] carried out a systematical simulation by classic free-volume theory to elucidate the damage mechanism in bulk metallic glasses. It was concluded that the fatigue endurance limit relied on different applied strain amplitude and cycling frequency.…”
Section: Introductionmentioning
confidence: 99%